European Phaseolus coccineus L. landraces: population structure and adaptation, as revealed by cpSSRs and phenotypic analyses. - Monica Rodriguez; Domenico Rau; Simonetta A Angioi; Elisa Bellucci; Elena Bitocchi; Laura Nanni; Helmut Knüpffer; Valeria Negri; Roberto Papa; Giovanna Attene (PLoS ONE, 2013)
Relatively few studies have extensively analysed the genetic diversity of the runner bean through molecular markers. Here, we used six chloroplast microsatellites (cpSSRs) to investigate the cytoplasmic diversity of 331 European domesticated accessions of the scarlet runner bean (Phaseolus coccineus L.), including the botanical varieties albiflorus, bicolor and coccineus, and a sample of 49 domesticated and wild accessions from Mesoamerica. We further explored the pattern of diversity of the European landraces using 12 phenotypic traits on 262 individuals. For 158 European accessions, we studied the relationships between cpSSR polymorphisms and phenotypic traits. Additionally, to gain insights into the role of gene flow and migration, for a subset of 115 accessions, we compared and contrasted the results obtained by cpSSRs and phenotypic traits with those obtained in a previous study with 12 nuclear microsatellites (nuSSRs). Our results suggest that both demographic and selective factors have roles in the shaping of the population genetic structure of the European runner bean. In particular, we infer the existence of a moderate-to-strong cytoplasmic bottleneck that followed the expansion of the crop into Europe, and we deduce multiple domestication events for this species. We also observe an adaptive population differentiation in the phenology across a latitudinal gradient, which suggests that selection led to the diversification of the runner bean in Europe. The botanical varieties albiflorus, bicolor and coccineus, which are based solely on flower colour, cannot be distinguished based on these cpSSRs and nuSSRs, nor according to the 12 quantitative traits.